Relationship of weight-adjusted waist index and developmental disabilities in children 6 to 17 years of age: a cross-sectional study - Li, Xueying; Zhou, Qi (Frontiers in Endocrinology, 2024)
The development of multiple system diseases is increased by obesity. However, the connection between obesity and developmental disabilities (DDs) in children is unclear. As an obesity index, the weight-adjusted waist index (WWI) assessed fat distribution and muscle mass. In this study, we examined the correlation between WWI and DDs among children 6 to 17 years of age. Methods: This study used data from the National Health and Nutrition Examination Survey database (NHANES) covering 2003 to 2018, which included the data of 17,899 participants between 6 and 17 years of age. Data regarding their waist circumference, weight, and DDs were collected via physical examinations and questionnaire, respectively. A person's WWI is calculated by dividing their waist circumference by their weight squared. The correlation between WWI and DDs was studied using weighted multiple logistic regression models. Additionally, a sensitivity analysis was conducted utilizing a generalized additive model and smooth curve fitting. Results: After adjusting for all covariates, WWI was positively related to DDs in children ages 6-17. Based on the sensitivity analysis, the correlation between the WWI and prevalence of DDs remained consistent across subgroups. Additionally, there was a J-shaped correlation between the WWI and the prevalence of DDs in children ages 6 through 11. Conclusion: Children 6-17 years of age with a high WWI were at greater risk for DDs; however, the causal relationships and potential mechanisms require further exploration.